Effect of spacing on performance of china aster (Callistephus chinensis L. Nees) under Malwa Plateau conditions of Madhya Pradesh - NIGAM, NISHA; KUMAR, ANUJ; SONKAR, PRIYAMVADA; GALLANI, ROSHAN; TIWARI, SHREJAL (Journal of Ornamental Horticulture, 2024)
During 2021-22 at the College of Horticulture in Mandsaur, India, this study was laid out in a factorial randomized design with three replications. Two cultivars of China aster (Callistephus chinensis), namely 'Arka Poornima' and 'Arka Archana', were examined under four distinct spacing conditions: 40 cm × 20 cm, 40 cm × 30 cm, 30 cm × 20 cm, and 30 cm × 30 cm (row to row×plant to plant). Different growth, flowering, quality and yield parameters were recorded and analyzed. Results revealed that narrower spacing (30 cm × 20 cm and 30 cm × 30 cm) led to increased plant height, leaf count and flower yield. Data indicate that plant height, number of leaves per plant, plant spread, number of branches/plant, days taken to 1st flower bud initiation, days taken to opening of flower bud, flower stalk length, number of flower/plant was significantly influenced by cultivar while, interactive effect was reported with days to opening of flower bud, flower diameter, flower yield/plant, flower yield/plot. The report concludes that spacing, cultivar and their interactions significantly affect the performance of China aster.